Fried Pupa of Silkworms Food Poisoning Outbreak due to Histamine Toxicity in Seven Provinces-Thailand, Dec 2007 - Jan 2008 - Mungaomklang, Anek; Teeyapant, Puntip; Sangsawang, Choopong; Pawun, Vichan; Kitphati, Rungrueng; Wuthiwan, Wattana; Hongchumpon, Nalinee; Niramitsantipong, Apinya; Sonthichai, Chaninan; Smithsuwan, Punnarai; Thonglek, Somkiet; Futrakul, Sita; et al. (Journal of Health Science of Thailand, 2018)
Fried insects, popular food in the country offered by sidewalk vendors, have never been previously reported as a cause of histamine toxicity outbreak. This investigation was confirming diagnosis and determining cause of outbreak. A descriptive study was conducted by analyzing data of clinical manifestation and food consumption of reported cases. Sources of silkworms were traced back from consumers (cases) to distributers. Sixty food items (insects and ingredients) were sent for biological, toxicological and chemical examinations. Totally, 118 cases were detected between December 24, 2007 and January 7, 2008 of which 66 percent were hospitalized while 91 percent of cases ate pupa of silkworms. Symptoms were nausea/ vomiting (83%), dizziness (78%), blurred vision (64%), mouth numbness (21%), chill (17%), palpitations (17%), muscle spasm (5%), urticaria (5%). Median incubation period was four hours (15 minutes to 22 hours). All cases completely recovered within a day. Severity was related to number of pupas eaten in a cluster. The outbreak subsided soon after wholesalers stopped distribution and recalled their imported pupas. In all sixty specimens general toxins could not be identified but only six specimens were reported positive for histamine substance (one mixed insects and five pupas). The high contamination of histamine (875 mg/kg) was found in one out of the five pupas specimens (US permitted maximal level; 50 mg/kg). Histamine poisoning is commonly associated with specific species of fish, but other foods which contain histamine-producing bacteria can produce histamine toxin. Good cold chain maintenance and limiting transportation delays will decrease risk of future outbreaks.